Exoffender accounts of successful reentry from prison - Hlavka, Heather R. (Journal of offender rehabilitation, 2015)
Reentry research often focuses on those who have recidivated, with little work addressing the experiences of those who successfully reintegrate into their communities. This study examines individual accounts of successful transitions from prison to community in the months and years postrelease. Interview data point to three metanarratives used to make sense of reentry: as reverence, as reunification, and as reconstruction. In different ways, each narrative centers on connections to important others through faith, family, or community. We discuss the legitimacy of the self-narratives offered, and add to a growing body of work exploring reentry via the lens of the exoffender.